DIAGNOSING THE SUCCESS OF THE BLUE OCEAN STRATEGY WITHIN THE FRAMEWORK OF HUBRISTIC LEADERSHIP IDEAS (World Economics and Finance Bulletin, 2025)
This research examines the applicability of Blue Ocean Strategy in the context of the key ideas of Hubris leadership. The study aims to understand how this leadership can be leveraged to achieve success within expansion strategies into new or emerging fields, where competition is less. The research indicates that there is a lack of knowledge about how hubris leadership can benefit from blue ocean strategy, despite the application of these concepts within the studied organization. The importance of the research lies in providing a scientific treatment for this problem, with a focus on diagnosing the extent of the application of hubristic leadership and the blue ocean strategy, and understanding the nature of the relationship between them within the University of the Future. The research adopted the descriptive analytical approach, and a questionnaire was used to survey the opinions of the research sample consisting of members of the university’s board of directors. The data were analyzed using the central tendency tools available in the SPSS-v23 program. The results showed that hubristic leadership plays an important role in the success of the implementation of the Blue Ocean Strategy at the University of the Future, as this leadership achieves a statistically highly positive impact, which confirms the validity of the main and sub-hypotheses of the research. Based on these results, the researchers recommend the need to host specialists and experts in the field of leadership and strategy to enhance human resources awareness of the importance and benefits of hubristic leadership and the Blue Ocean Strategy.